Foreign direct investment inflows and economic growth in Singapore : an empirical approach - Le, Ha-Chi (2021)
The aim of this paper is to examine the impacts of inward foreign direct investment (FDI) on economic growth in Singapore. The dataset during the period 1970-2018 was analyzed based on an extended Cobb-Douglas production function. Autoregressive distributed lag (ARDL) models, with accounting for a structural break, were utilized to assess the linkages among the variables. Two proxies for trade openness and two measures of financial developments were employed for comparison. The results show that, while there are multiple drivers of the country’s economic growth in the short run, only FDI and exports are long-term determinants of Singapore’s economic growth. The findings suggest that FDI plays a crucial role in assisting the country’s economic development and the results are relatively robust to different measures of trade and finance. This implies that Singapore’s “economic miracle” is indeed attributable to effective strategies in managing inward FDI and promoting trade activities and that more emphasis should be put on FDI in assisting national economic development.